2006
DOI: 10.1097/01.bcr.0000216457.25875.f4
|View full text |Cite
|
Sign up to set email alerts
|

Base Deficit and Alveolar–Arterial Gradient During Resuscitation Contribute Independently But Modestly to the Prediction of Mortality After Burn Injury

Abstract: The main determinants of mortality after burn injury that can be measured on admission include age, total burn size (% burn), and inhalation injury (INHAL). Other variables, measured during resuscitation, may provide additional information about injury severity. We assessed the utility of early arterial blood gas (ABG) data in predicting mortality after burn injury. Data were limited to samples obtained during the first 2 days after burn injury and to those obtained during high-frequency percussive ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Previous studies of burn resuscitation have demonstrated that base excess is a predictor of mortality in addition to age, TBSA, and inhalation injury. 34 Amelioration of acidosis in the 1:1 group, by correcting acidosis, may alter the trajectory of outcomes after burn injury. Further prospective studies will be necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of burn resuscitation have demonstrated that base excess is a predictor of mortality in addition to age, TBSA, and inhalation injury. 34 Amelioration of acidosis in the 1:1 group, by correcting acidosis, may alter the trajectory of outcomes after burn injury. Further prospective studies will be necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Abnormalities of base deficit and lactate have been found to co-occur with appropriate urine output and blood pressure in burn patients during resuscitation. [7][8][9]11,13,14 Although these abnormalities suggest inadequate resuscitation, their precise role in the titration of therapy for burn shock remains ambiguous. Perhaps most important, were more aggressive fluid resuscitation to be pursued on the basis of measures of serum lactate or base deficit, the potential exists for increased secondary complications of resuscitation, including compartment syndromes and pulmonary failure.…”
Section: Discussionmentioning
confidence: 99%
“…19 A more recent study of 162 patients with burn showed a correlation between BE and mortality. 20 A burn research group showed both retrospectively 21 and prospectively 22 that traditional end points such as MAP and urine output may be normal in the presence of a significantly abnormal BE. Similar to the patients with trauma, normalization of the BE in 24 hours is associated with decreased mortality.…”
Section: Base Excess In Burnsmentioning
confidence: 98%